Role of physical therapy in women’s health - Faryal Zaidi; Ishaq Ahmed (Journal of the Pakistan Medical Association, 2022)
Women’s health indicates an intimate health of a woman that is different from that of a man in many peculiar terms. The way a woman manifests her health and disease is quite different than that of a man with respect to her unique biological, behavioural and social perspectives. Although the biological differences are associated with high risk of developing ill health, the gender-differentiated access to medical interventions and basic education along with other socioeconomic factors play an important role in women’s primary health care.1,2 In the whole world, woman’s health is directly related to her reproductive health i.e. menstruation, birth control and menopause while ignoring all other health related issues.2,3 The WHO states that an undue focus on reproductive health deprives all women from getting good quality health care.4 So, the replacement of "Women’s Health" with "The Health of Women" is a pressing need of time as women require health care and health care system more than that of men not just due to their reproductive and sexual health needs but also they have more chronic conditions like Diabetes, Osteoporosis, Cardiovascular diseases, mental illness and malignancies.5